KEDUDUKAN HUKUM AKTA PPAT SETELAH TERBITNYA SERTIPIKAT KARENA PERALIHAN HAK ATAS TANAH - Saraswati, Made Putri; Utama, I Made Arya; Putra Santika, Ida Bagus Agung (Acta Comitas, 2018)
According to Article 1 Number 4 and Article 2 section (1) Government Regulation Number 37 Of 1998, explained that PPAT deed have two function which are as evidence on legal action to land rights title and as a registration instrument for the data change of the land registration. When the transfer of land rights title occurs, the function of PPAT deed as a registration instrument is completed and leaves the PPAT deed as evidence on legal action to land rights title. Likewise, if the next rights transfer occurs, it will also re-leave another PPAT deed as evidence on legal action to land rights title. There are two legal issues were reviewed toward to the title of PPAT deed related to liability of PPAT to keep the deed, that is (1) the legal standing of PPAT deed which used as a basis of certificate issuance after the next rights transfer and (2) The liability of PPAT on the deed which encountered the next transfer of rights related to the PPAT obligation to keep the deed. The type of research used in this thesis is normative legal research refers to the void of norm according with the standing of PPAT deed after the land rights title transfer that connected to the responsible of PPAT which related to their liability on the deed. The research approach of this thesis consists by the statutory approach and conceptual approach.  Based on the result of this research, the conclusion is the legal standing of PPAT deed that encountered the land rights title, in the internal interest of the national land authority can be categorized as static archives because the legal standing of PPAT deed as active dynamic archive only during the processing until the certificate issued. Meanwhile, in the external interest PPAT deed is a living or active document which is the consequence of its position as an evidence on legal action. PPAT deed in the external interest can be categorized as active archives for 25 years. The purpose of the deed can be said completed, if the legal action that mean in the deed has been final. In the event that the PPAT deed has encountered the next transfer of rights, it stops the liability of the PPAT, even though the land rights do not transfer, the legal norm refers to 25 years. Keyword : PPAT Deed, Registration Instrument, Evidence on Legal Action, The Transfer of Land Rights.